1987
DOI: 10.1073/pnas.84.11.3550
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the tyrosine hydroxylase gene by glucocorticoid and cyclic AMP.

Abstract: Glucocorticoid and cyclic AMP increase tyrosine hydroxylase (TH) activity and mRNA levels in pheochromocytoma cultures. The transcriptional activity of the TH gene, as measured by nuclear run-on assay, is also increased when cultures are treated with the synthetic glucocorticoid dexamethasone or agents that increase intracellular cyclic AMP, such as forskolin and 8-BrcAMP. Both inducers effect transcriptional changes within 10 min after treatment and are maximal after 30 min for forskolin and after 60 min for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
174
1

Year Published

1990
1990
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(185 citation statements)
references
References 45 publications
10
174
1
Order By: Relevance
“…The upstream promoter regulatory sequences for the genes encoding TH (Lewis et al 1987;Piech-Dumas and Tank 1999;Piech-Dumas et al 2001) and DBH (Shaskus et al 1992;Kim et al 1994b) have functional CREs that are cAMP-responsive, and these CREs participate in phorbol ester-mediated PKC activation (Shaskus et al 1992;Piech-Dumas et al 2001). A canonical CRE has not been identified in the rat PNMT gene promoter (Ross et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The upstream promoter regulatory sequences for the genes encoding TH (Lewis et al 1987;Piech-Dumas and Tank 1999;Piech-Dumas et al 2001) and DBH (Shaskus et al 1992;Kim et al 1994b) have functional CREs that are cAMP-responsive, and these CREs participate in phorbol ester-mediated PKC activation (Shaskus et al 1992;Piech-Dumas et al 2001). A canonical CRE has not been identified in the rat PNMT gene promoter (Ross et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The genes coding for tyrosine or tryptophan hydroxylase, whose proteins are closely related to PAH, show tissue-specific expression and are hormone inducible. However, the promoter structures of these three genes are different (5,32).…”
Section: Discussionmentioning
confidence: 99%
“…Inspection of the rat TH promoter (Harrington et al 1987) revealed a potential regulatory element between positions -205 and -193 with homology to a previously characterized regulatory sequence, the FSE, which is found in genes regulated during adipocyte differentiation (Distel et al 1987). Within the FSE lies a sequence homologous to the 8-bp AP-l-binding site found in both viral and animal genomes (Angel et al 1987;Lee et al 1987a, b).…”
Section: Functional Activity Of the Th-fse Dna Sequencementioning
confidence: 95%
“…Regulatory DNA regions of the rat TH promoter. The 5'-untranscribed DNA region of the rat TH promoter (Harrington et al 1987)is shown and contains a CRE {{Hyman et al 1988) located at positions -45 to -3 8 and the TH-FSE DNA element located at positions -205 to -193. The TH-FSE shares homology with the FSE2 DNA region of the adipocyte-specific gene aP2 (Distel et al 1987).…”
Section: Functional Activity Of the Th-fse Dna Sequencementioning
confidence: 99%
See 1 more Smart Citation